From Market Efficiency to Firm Valuation: The Role of Digital Finance - Su, Aoran (International Journal of Global Economics and Management, 2026)
With the penetration of the digital technology into the financial sector becoming increasingly pervasive, most of the scholarly work has centered on the way this change alters financial service supply models, but have not considered its serious impact on the capital markets and the value of listed companies. With the help of the PKU-DFIIC, A-share listed companies financial report, and exchange trading data, this paper investigates the relationship among these three factors, i.e., the development of digital finance, the efficiency of the market and the valuation of companies. Built upon the consensus and gaps within the current literature it takes apart what digital finance really does in practice regarding information transfer, capital movement and resource distribution and outlines the whole road of how enhanced market efficiency is transmitted to company value. Research has found that digital finance can mitigate information barriers, optimize the overall trading environment, and alleviate the problem of firm value mismatch by improving financing conditions and governance mechanisms. Firms of different sizes and property rights have varying abilities to capture the benefits from digital finance. By analyzing the limitations of the industry reality, this paper provides actionable insights for optimizing the construction of the capital market and managing firm value.